A coupled thermo-mechanical bond-based smoothed particle dynamics model for simulating thermal cracking in rocks. (15th April 2022) - Mu, Dianrui; Li, Zhiming; Tang, Aiping; Liu, Qiang; Huang, Delong
Highlights: A smoothed particle dynamics (SPD) method is proposed for crack propagation. The SPD method significantly improves calculation efficiency. Three failure mechanisms of concrete beams are obtained. A thermo-mechanical coupling TM-BB-SPD model is established for thermal cracking. Thermal cracking mode of the rock disc is related to the thermal expansion coefficient. Abstract: A smoothed particle dynamics (SPD) method was proposed for crack propagation analysis. The computational efficiency of this method was significantly better than the traditional smoothed particle hydrodynamics (SPH) method. In the SPD method, the motion equations were approximated by a Lagrange kernel determined by the coordinates of the material in the initial configuration. A coupled thermo-mechanical bond-based smoothed particle dynamics (TM-BB-SPD) model was proposed for simulating the thermal cracking process of rocks. In the SPD program, the thermal cracking behaviors of rock, such as crack initiation and propagation, were dynamically tracked by capturing the damage state of virtual bonds. The robustness and accuracy of the proposed SPD method and TM-BB-SPD model were verified using two benchmark examples. The numerical results were in good agreement with the experimental results and analytical solutions. In addition, the effects of the thermal expansion coefficient and homogeneity index on the mode of thermal cracking in the rock disc were also investigated. The numerical results were also in good agreement with previous experimental observations. Moreover, the numerical results showed that with an increase in the homogeneity index, the mode of crack propagation in rock gradually changed from non-smooth to smooth types of fracture.